Pulmonary Nodule in a Bitch - 18FDG-PET/CT for Discriminating the Origin and Malignancy of the Lesion - Jung, Hye-In; Koo, Yoonhoi; Chae, Yeon; Yun, Taesik; Kim, Hakhyun; Kang, Byeong-Teck (Acta Scientiae Veterinariae, 2025)
Background: Lung cancer is the leading cause of cancer-related deaths in humans. In dogs and cats, lung cancer is also a notable cause of death, with metastatic lung cancer being more common than primary lung cancer in dogs. Differentiating benign from metastatic lung nodules is important because treatment plans can differ. Metastatic tumors are typically treated medically, whereas primary cancers and benign lung nodules are managed surgically. Advanced imaging techniques, such as 18F-fluorodeoxyglucose positron emission tomography/computed tomography, enhance the detection and diagnosis of lung nodules. This case report aimed to describe the role of 18F-fluorodeoxyglucose positron emission tomography/computed tomography in identifying the origin of a lung nodule in a bitch. Case: A 11-year-old intact bitch Golden Retriever was referred for evaluation and surgical resection of a splenic mass. Ultrasonography identified a well-demarcated, round mass measuring 7.6 × 6.9 cm at the splenic tail, suggesting a malignant splenic tumor owing to its size and remarkable change in splenic contour. 18F-fluorodeoxyglucose positron emission tomography/computed tomography was performed to assess the malignancy and metastasis of the splenic tumor, revealing a pulmonary nodule with increased 18F-fluorodeoxyglucose uptake indicative of metastasis, which had not been detected on radiography. The maximum mean standardized uptake value of the abnormal lesions were as follows: splenic tail mass, 2.91 and 2.17; mammary gland mass, 5.22 and 3.81; and pulmonary nodule, 4.16 and 3.37, respectively. These results suggest possible inflammatory or malignant lesions in the mammary gland mass and pulmonary nodule. Based on the 18F-fluorodeoxyglucose-positron emission tomography/computed tomography findings, if the pulmonary nodule resulted from metastasis, its origin was more likely to be a mammary gland mass rather than a splenic mass. Histopathology following splenectomy and mammary gland resection were performed at the owner’s request, and the bitch was diagnosed with splenic hematoma and high-grade mammary basaloid ductular carcinoma with focal lymphatic vessel invasion, respectively. The animal died of dyspnea 4 months post-surgery. Discussion: This case report highlights the utility of 18F-fluorodeoxyglucose- positron emission tomography/computed tomography for defining the origin of pulmonary lung nodules in dogs. The 18F-fluorodeoxyglucose- positron emission tomography/computed tomography results provided critical information that influences diagnostic and treatment approaches. This case demonstrates the potential of 18F-fluorodeoxyglucose- positron emission tomography/computed tomography as a diagnostic tool for providing information on tumor malignancy and origin. In addition, the integration of 18F-fluorodeoxyglucose- positron emission tomography/computed tomography with computed tomography provides both anatomical and functional information, providing a comprehensive assessment superior to that provided by computed tomography alone. Future perspectives include further evaluation of 18F-fluorodeoxyglucose- positron emission tomography/computed tomography in larger cohorts of veterinary patients to establish its role in routine clinical practice for diagnosing the origin and malignancy of canine lung lesions. Keywords: metastatic lung cancer, 18F-FDG, positron emission tomography, mammary gland tumor, splenic mass, canine mammary glands.